2019
DOI: 10.1080/19476337.2019.1680579
|View full text |Cite
|
Sign up to set email alerts
|

Multi-residue analysis of 203 pesticides in strawberries by liquid chromatography tandem mass spectrometry in combination with the QuEChERS method

Abstract: Herein, a QuEChERS (quick, easy, cheap, effective, rugged, and safe) procedure together with liquid chromatography and tandem mass spectrometry was applied to the multi-residue analysis of 203 pesticides in strawberries. To reduce the amount of co-eluents, we compared several dispersive solidphase extraction cleanup procedures and found that cleanup using octadecylsilane provided the best recoveries. Spiked-sample recoveries of 70-120% with relative standard deviations of <20% were obtained for all tested pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…As a result, 250, 247, 262, and 237 pesticide targets gave ideal recoveries at each of the spiked levels in red onion, pakchoi, king oyster mushroom, and black tea, respectively (Tables S6–S9). As shown in Table S10, the developed method was compared with other methods based on QuEChERS, dispersive liquid–liquid microextraction (DLLME), and solid-phase micro-extraction (SPME), suggesting a satisfactory performance of the automated workflow. …”
Section: Resultsmentioning
confidence: 98%
“…As a result, 250, 247, 262, and 237 pesticide targets gave ideal recoveries at each of the spiked levels in red onion, pakchoi, king oyster mushroom, and black tea, respectively (Tables S6–S9). As shown in Table S10, the developed method was compared with other methods based on QuEChERS, dispersive liquid–liquid microextraction (DLLME), and solid-phase micro-extraction (SPME), suggesting a satisfactory performance of the automated workflow. …”
Section: Resultsmentioning
confidence: 98%
“…Several previous studies have shown that all of the three versions (original, AOAC, and EN) of the QuEChERS method were effective for extraction and purification of thiacloprid in various matrices (Abdallah & Malhat, 2019; Chen et al, 2014; Song et al, 2019; Suganthi & Bhuvaneswari, 2018). Among them, best recovery was achieved through the QuEChERS EN method.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate analysis of field‐supervised sample is necessary for IT MRL that might be an outcome of a robust method. Thiacloprid has been detected in various matrices using different analytical methodologies (Abdallah & Malhat, 2019; Banerjee & Banerjee, 2012; Banno & Yabuki, 2020; Chen, Tao, McLean, & Lu, 2014; Kovacova et al, 2013; Lazić, Šunjka, Begović, & Vuković, 2015; Sahoo, Mandal, Kaur, Battu, & Singh, 2013; Song, Yoo, & Nam, 2019; Suganthi & Bhuvaneswari, 2018; Wang, Guan, & Zhang, 2011; Yun‐long, Jia‐lun, Matthias, & Wilfried, 2007). Among them LC is the most commonly used instrument in combination with traditional or mass spectrometry detector.…”
Section: Introductionmentioning
confidence: 99%
“…Co-eluted interferences in samples may not be a problem [ 17 , 18 , 19 ]. Many laboratories have used “Quick, Easy, Cheap, Effective, Rugged, and Safe” (QuEChERS) methods with good results and high recoveries [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%